Gallery Walk in Action: Pre-Service Teachers' Visions for Enhancing Speaking Skills in an Indonesian EFL Classroom - Nadiah Ma'mun; Zahra Al Fauziah (Journal of English Education Studies, 2025)
This study explores pre-service English teachers’ perspectives on implementing the Gallery Walk strategy to enhance EFL students’ speaking skills. Using a qualitative case study design, the participants consisted of five pre-service teachers who conducted their teaching practicum at one of public schools in Central Java. Data were collected through open-ended questionnaires, and classroom observations. The findings reveal that the Gallery Walk strategy was perceived as an effective, interactive, and student-centered approach that encouraged students’ participation, boosted confidence, and improved fluency, vocabulary use, and argument structure. Despite challenges related to time management, student shyness, and material preparation, the teachers adapted through reflection and instructional adjustment. These results suggest that Gallery Walk is a feasible and beneficial strategy for enhancing speaking skills in EFL contexts.